IMPACT OF SOCIAL MEDIA ON SALES FUNNELS IN B2C AND B2B SEGMENTS IN THE REPUBLIC OF NORTH MACEDONIA - Kiselicki, Martin; Josimovski, Saso; Pulevska ivanovska, Lidija; Santa, Mijalche (National and University Library of the Republic of Srpska, 2021)
The research focuses on introducing social media platforms as either a complementary or main channel in the company sales funnel. Internet technologies and Web 2.0 continue to provide innovations in digital marketing, with the latest iteration being lead generation services through social media. Data shows that almost half of the world population is active on social media, with the new Generation Alpha being projected to be entirely online dependent and proficient in the use of new technologies. The paper provides an overview of the digitalization of sales funnels, as well as the benefits that social media platforms can offer if implemented correctly. Secondary data provides the basis for transforming sales funnels with social media, where previous research provides limited data on the effectiveness of these types of efforts. Primary data demonstrates that introducing social media platforms can provide improvements of up to 3 to 4 times in analyzed case studies, as well as the shorter time when deciding about purchase in use case scenarios. Social media advertising can also be utilized to shorten the sales funnel process and serve as a unified point of entrance and exit in the first few stages.